2010
DOI: 10.1164/rccm.201001-0108oc
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Attenuates Intermittent Hypoxia-induced Spatial Learning Deficits and Oxidative Stress

Abstract: Rationale: Exposure to intermittent hypoxia (IH), such as occurs in sleep-disordered breathing, is associated with substantial cognitive impairments, oxidative stress and inflammation, and increased neuronal cell losses in brain regions underlying learning and memory in rats. Physical activity (PA) is now recognized as neuroprotective in models of neuronal injury and degeneration. Objectives: To examine whether PA will ameliorate IH-induced deficits. Methods: Young adult Sprague-Dawley rats were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 69 publications
(97 reference statements)
0
32
0
Order By: Relevance
“…The present study demonstrates that 12 hours of SF during the daylight period for 14 days, which aims to mimic sleep apnea, interferes with spatial learning and retention memory tests in a well-defined hippocampus-dependent learning and memory task (14,42). The SF-induced performance deficits in the water maze could be mediated by a disturbance in hippocampaldependent memory consolidation.…”
Section: Discussionmentioning
confidence: 61%
“…The present study demonstrates that 12 hours of SF during the daylight period for 14 days, which aims to mimic sleep apnea, interferes with spatial learning and retention memory tests in a well-defined hippocampus-dependent learning and memory task (14,42). The SF-induced performance deficits in the water maze could be mediated by a disturbance in hippocampaldependent memory consolidation.…”
Section: Discussionmentioning
confidence: 61%
“…Development of rodent models mimicking components of OSA have yielded important insights into the mechanistic pathways underlying neural injury in the context of IH and SF, and have particularly pointed out the critical role of oxidative stress and inflammation-mediated neural injury in this context (Nair et al 2011b, Nair et al 2011a). Earlier studies from our laboratory indicated that exogenous growth hormone (GH) administration was anti-apoptotic and neuroprotective in the context of IH-induced neuronal injury, and that physical activity-associated neuroprotective effects during IH were mediated, at least in part, by endogenous increases in neuronal expression of IGF-1 (Li et al 2011, Gozal et al 2001, Gozal et al 2010). However, the possibility that growth hormone-releasing hormone (GHRH) may also be neuroprotective was not explored.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the expression of these 4 genes is tightly regulated in the CNS by HIF-1α (Freeman and Barone, 2005;Acker and Acker, 2004), and plays a major protective role in hypoxia and ischemia-induced brain injury (Sharp et al, 2004;Fan et al, 2009). SDB is associated with suppression of growth hormone (GH) secretion (Meston et al, 2003;Cooper et al, 1995;Saini et al, 1993), the presence or absence of cognitive deficits is dependent on the serum levels of IGF-1 at any given level of severity of SDB, and in rodents, physical activity that stimulates IGF-1 is neuroprotective, suggesting that GH suppression may play a role in SDB-associated neurocognitive deficits (Gozal et al, 2009;Gozal et al, 2010). Based on these considerations, the aims of present study were to determine whether similar to IH, CH is associated with spatial learning and memory deficits, and whether exogenous systemic administration of GH will protect the brain from IH-induced neuronal apoptosis and consequent functional deficits.…”
Section: Introductionmentioning
confidence: 99%